Proceedings of the 2022 ACM on Asia Conference on Computer and Communications Security 2022
DOI: 10.1145/3488932.3517411
|View full text |Cite
|
Sign up to set email alerts
|

Port Contention Goes Portable

Abstract: Microarchitectural side-channel attacks can derive secrets from the execution of vulnerable programs. Their implementation in web browsers represents a considerable extension of their attack surface, as a user simply browsing a malicious website, or even a malicious third-party advertisement in a benign cross-origin isolated website, can be a victim.In this paper, we present the first port contention side channel running entirely in a web browser, despite a highly challenging environment. Our attack can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Mitigating Port Contention with WASM-MUTATE Rokicki et al [39] showed the practicality of a covert sidechannel attack using port contention within WebAssembly code in the browser. This attack fundamentally relies on the precise prediction of Wasm instructions that trigger port contention.…”
Section: Discussionmentioning
confidence: 99%
“…Mitigating Port Contention with WASM-MUTATE Rokicki et al [39] showed the practicality of a covert sidechannel attack using port contention within WebAssembly code in the browser. This attack fundamentally relies on the precise prediction of Wasm instructions that trigger port contention.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of identity theft and authentication attacks, device identification has become an important topic in recent years. However, most fingerprint methods such as [19,30] rely on the differences between machines with different software or hardware. Consequently, these kind of fingerprints would not be able to distinguish between identical devices in the same environment.…”
Section: Discussionmentioning
confidence: 99%
“…As temperature and power are not the only CPU micro-architectural properties, we infer that more features can be used in the identification, which will improve its robustness, accuracy, and stability. Furthermore, we believe that a power consumption feature can be added to existing authentication methods [30,19,7,38,40]. Artifact Availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation